Distribution of Particulate Organic Carbon within Water Stable Aggregates of Inceptisol Profiles under different Land Use - Shreyasi Gupta Choudhury,; P.K. Bandyopadhyay,; S.Mallick, (Journal of Soil and Water Conservation, 2022)
Particulate organic C (POC) is the physically protected C when soil organic C(SOC) is stabilized within microaggregates (0.1-0.25 mm) and macroaggregates (0.25-2 mm) of water stable aggregates (WSA). This study evaluated carbon distribution within WSA at depth off allow and cultivated profiles of Inceptisol in the research farm of Bidhan Chandra Krishi Viswavidyalaya, West Bengal Results showed that cultivation reduced SOC to the extent of 25.3% as compared to fallow which reflects in reduction of macroaggregates. Macroaggregated C was observed 31.2% higher and microaggregated C was found 16% lower under fallow than cultivated soils. The impacts of macroaggregation were dependent on the amount of C aggradations by the crop species. The POC values below 0.5 mm size classes strongly influenced dynamics of carbon cycling in soils and explained higher accretion (15.5%) in the microaggregate fraction for the cultivated soils as compared to fallow. The POC could well be protected in sub-surface soil layers than the surface soil layers as a means of C aggradations. The aggregate stability and mean weight diameter were strongly and positively correlated with clay and SOC. Both macro and microaggregated C along with microbial biomass C (MBC) positively and significantly influenced structural stability. A positive relationship among POC and clay in our results may explain the possibility of C stabilization in clay of this soil.